Exploratory Study of Textile Undergraduates’ Knowledge and Perception towards Eco-Friendly Clothing in Bangladesh - Upama Nasrin Haq; Tania Akhter Ite (Tekstilec)
Environmentalism leads to the concept of eco-friendly clothing (EFC) and its popularity is advancing all over the world. In-depth knowledge acquisition regarding EFC has become a fundamental requirement for Bangladeshi Textile undergraduates as they are the future professionals in the EFC sector. To ascertain the knowledge level and perception of the Bangladeshi textile undergraduates regarding EFC was the aim of this study. In this exploratory study, a self-administered questionnaire was used to collect data through purposive sampling from the students enrolled into the Bangladesh undergraduate Textile Engineering programme. The respondents were 282 students of the fourth year of different universities located in Dhaka city. Descriptive statistics were used to represent the findings of the research. The results showed that 82.3% of the respondents were informed about EFC, 35.8% were knowledgeable regarding EFC raw materials and 53.02% were cognisant about the production process. 89.4% of the respondents expected one particular course on EFC in curriculum and 94% wanted to contribute towards EFC in the future. The study revealed that undergraduates have a knowledge gap regarding EFC, while their willingness to learn and contribute is very optimistic. The findings suggested that the evaluation and modification of the curriculum for EFC and incorporation of EFC courses can lessen this salient gap.